Evaluation of Risk Factors for Hepatotoxicity in Patients Receiving Antitubercular Four Drugs Regimen in Initial Two Months - Faiz, Saifun Nahar; Chowdhury, Nasreen; Khan, Md Aminul Haque; Parvin, Rukhsana (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Tuberculosis (TB) is a major public health problem in Bangladesh since long before. Standard first line drugs are isoniazid, rifampicin, pyrazinamide and ethambutol. Of these, isoniazid, rifampicin and pyrazinamide have been observed to have hepatotoxic potentials. Drug Induced Hepatotoxicity (DIH) is an important and commonly encountered adverse effect with anti-TB treatment. A higher risk of hepatotoxicity has been reported in Bangladeshi patients than in their western counterparts. The reasons for the higher rate of hepatotoxicity in Bangladeshi patients are unclear. Objectives: To know the possible risk factors for the development of drug induced hepatotoxicity and to see their association with hepatoxicity in patients receiving antitubercular treatment as per National Tuberculosis Control Programme. Materials and Methods: In this cross sectional prospective study, 100 freshly diagnosed pulmonary tuberculosis patients attending the Medicine Outpatient Department, admitted in Chittagong Medical College Hospital, DOTS center in the hospital were selected for the study. Results: In this study we found twenty percent patients (20%) developed Antituberculosis Treatment (ATT) induced hepatotoxicity and most of them were in the age group of 5065 years. Among the patients who developed hepatotoxicity (DIH) 27% patients were in BMI 18.5 group. The patients presenting with radiologically severe Pulmonary Tuberculosis (PTB) developed higher hepatotoxicity than patients with milder disease. The patients with history of high alcohol intake and with pre-treatment hypoalbuminemia were also found to have higher drug induced hepatotoxicity as compared to non-alcoholics and normal serum albumin level respectively. This study showed the evidence of ATT induced liver damage in twenty percent (20%) patients. Among them 05% cases developed overt drug induced hepatotoxicity (DIH) and remaining 15% cases had asymptomatic elevation of serum ALT, AST and bilirubin levels. The remaining 80% cases did not show any significant change in their serum bilirubin and/or enzyme levels as compared to pre-treatment levels. Conclusion: Advanced age, high alcohol intake, radiologically severe disease before treatment and pretreatment hypoalbuminemia are predisposing factors for the development of ATT induced hepatotoxicity. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22873 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 15-18